Effect of oxidizing atmosphere on the electrical properties of SrBi4Ti4O15 thin films obtained by the polymeric precursor method - Simões, Alexandre Zirpoli [UNESP]; Ramirez, M. A. [UNESP]; Riccardi, C. S. [UNESP]; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2008)
Strontium bismuth titanate (SrBi4Ti4O15) thin films were deposited on (111) Pt/Ti/SiO2/Si Substrates by spin coating from the polymeric precursor method. Annealing in static air and dynamic oxygen atmosphere was performed at 700 degrees C for 2 h. The films were characterized by X-ray diffraction, atomic force microscopy and electric properties. The dielectric properties of SrBi4Ti4O15 films were found to be remarkably sensitive to the annealing atmosphere. The C-V characteristics of the metal-ferroelectric metal structure showed a typical butterfly loop that confirms the ferroelectric properties of the film related to the domains switching. SrBi4Ti4O15 thin films annealed in oxygen atmosphere showed lower ferroelectric behavior indicating a weak ferroelectricity along c-axis direction. Published by Elsevier Masson SAS.
Keywords: Thin films; Atomic force microscopy; Dielectric properties